Impact of water quality/quantity on agricultural policy - Ringler, Claudia (2018)
Presented by IFPRI Senior Research Fellow Claudia Ringler at the International Workshop on Innovation in Modelling Coupled Natural and Human Systems Related to Water, Tübingen, May 31 & June 1, 2017.